11(x-2)=7x-11

Simple and best practice solution for 11(x-2)=7x-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11(x-2)=7x-11 equation:


Simplifying
11(x + -2) = 7x + -11

Reorder the terms:
11(-2 + x) = 7x + -11
(-2 * 11 + x * 11) = 7x + -11
(-22 + 11x) = 7x + -11

Reorder the terms:
-22 + 11x = -11 + 7x

Solving
-22 + 11x = -11 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-22 + 11x + -7x = -11 + 7x + -7x

Combine like terms: 11x + -7x = 4x
-22 + 4x = -11 + 7x + -7x

Combine like terms: 7x + -7x = 0
-22 + 4x = -11 + 0
-22 + 4x = -11

Add '22' to each side of the equation.
-22 + 22 + 4x = -11 + 22

Combine like terms: -22 + 22 = 0
0 + 4x = -11 + 22
4x = -11 + 22

Combine like terms: -11 + 22 = 11
4x = 11

Divide each side by '4'.
x = 2.75

Simplifying
x = 2.75

See similar equations:

| 12x+13=7x+20 | | 32=x+x+(x+2)+(x+2) | | 50x^2-18x+6=0 | | 50x^2-18+6=0 | | 4xy+xy= | | 0.36(6)+0.06x=0.18(6+x) | | 1,006,458=x | | -18x=-13 | | 27=-5x | | 7.71=2(3.14)(x) | | 2x^2+17x-5=0 | | 4/3x^2+14/3x+2=0 | | 2x^2-17x-5=0 | | 2sin^2(x)+3sin(x)+1=0 | | -11t+16=-6 | | 9z+-12+-2z+5=0 | | 15p+3n-2m+10n= | | 9z-12-2z+15=0 | | 3x^2-30x+45=0 | | 4x^6+x^5-18x^4= | | x^2-44x=-c | | 15-6x=18-5x | | 4x^2-20x=24 | | 5m+3n-2m+10n= | | 4x^2(x+1)-9(x+1)=0 | | 49v^2-28vu+4u^2=0 | | 2=-4.9(2)+19.6(2)+1 | | 125-7x=11x+19 | | 0=x^2-24+c | | 3(x-4)-(6x+3)=3(4x+1) | | 19/10=c/23 | | x+2-3x-4+5x-6+7x-8=9x+10-11x+12 |

Equations solver categories